A Method for Assessing the Risk of Development of Disease Complications with Metabolic Syndrome Based on the Cumulative Distribution Function - Andreasyan, L. K. («Պոլիտեխնիկ» տպ.)
It is relevant to assess the risks of related diseases based on the electronic data of patients in order to prevent the progress of further complications of metabolic syndrome (MS). This article describes the Archimedean copula-based method of assessing the risks of developing related diseases based on diagnosis and risk factors associated with complications and readmissions. Արդիական է կանխել մետաբոլիկ համախտանիշով (ՄՀ) հիվանդությունների հետագա բարդությունների զարգացումը՝ գնահատելով հիվանդների էլեկտրոնային տվյալների հիման վրա հարակից հիվանդությունների ռիսկերը: Նկարագրվում է ՄՀ ունեցող հիվանդների ախտորոշումների և ռիսկի գործոնների հիման վրա բարդությունների ու հետհոսպիտալացման հետ կապված հարակից հիվանդությունների զարգացման ռիսկերի գնահատման Արքիմեդյան կոպուլահենքով մեթոդը։ Показана актуальность оценки рисков сопутствующих заболеваний на основании электронных данных пациентов с целью предупреждения прогрессирования дальнейших осложнений метаболического синдрома (МС). Описан метод оценки рисков развития сопутствующих заболеваний на основании диагнозов и факторов риска, связанных с осложнениями и повторными госпитализациями у больных МС на основе Архимедовы копулы.
Keywords: Computer science and informatics